Strong cardiovascular prognostic implication of quantitative left atrial contractile function assessed by cardiac magnetic resonance imaging in patients with chronic hypertension - Tsang Sui; Khin Maung; Jerosch-Herold Michael; Steel Kevin; Kaminski Matthew; Hauser Thomas; Kwong Raymond Y (Journal of Cardiovascular Magnetic Resonance, 2011)
Abstract Background Progressive left ventricular (LV) diastolic dysfunction due to hypertension (HTN) alters left atrial (LA) contractile function in a predictable manner. While increased LA size is a marker of LV diastolic dysfunction and has been shown to be predictive of adverse cardiovascular outcomes, the prognostic significance of altered LA contractile function is unknown. Methods A consecutive group of patients with chronic hypertension but without significant valvular disease or prior MI underwent clinically-indicated CMR for assessment of left ventricular (LV) function, myocardial ischemia, or viability. Calculation of LA volumes used in determining LA emptying functions was performed using the biplane area-length method. Results Two-hundred and ten patients were included in this study. During a median follow-up of 19 months, 48 patients experienced major adverse cardiac events (MACE), including 24 deaths. Decreased LA contractile function (LAEFContractile) demonstrated strong unadjusted associations with patient mortality, non-fatal events, and all MACE. For every 10% reduction of LAEFContractile, unadjusted hazards to MACE, all-cause mortality, and non-fatal events increased by 1.8, 1.5, and 1.4-folds, respectively. In addition, preservation of the proportional contribution from LA contraction to total diastolic filling (Contractile/Total ratio) was strongly associated with lower MACE and patient mortality. By multivariable analyses, LAEFContractile was the strongest predictor in each of the best overall models of MACE, all-cause mortality, and non-fatal events. Even after adjustment for age, gender, left atrial volume, and LVEF, LAEFContractile maintained strong independent associations with MACE (p < 0.0004), all-cause mortality (p < 0.0004), and non-fatal events (p < 0.0004). Conclusions In hypertensive patients at risk for left ventricular diastolic dysfunction, a decreased contribution of LA contractile function to ventricular filling during diastole is strongly predictive of adverse cardiac events and death.